Greece investment guide (Athens : Hellenic Industrial Development Bank, 1969)
This publication is a part of the effort been made to attract foreign investment capital to Greece and at the same time to continue and improve upon earlier attempts to serve and advise private business, especially in the field of manufacturing.
Includes bibliographical footnotes.
hza 01/02/2019
Loans
Keywords: Investments, Foreign; Business enterprises, Foreign; Greece